Populasi dan Spesies Serangga Hama di Gudang dengan Penciri Struktur dan Sanitasi yang Berbeda di Dua Pasar Lokal di Kecamatan 7 Ulu dan Plaju, Palembang Sumatera Selatan - Indayani, Indayani; Herlinda, Siti; Yulistin, Eka; Setyawati, Anita; Oktaviani, Oktaviani; Anggraini, Erise; Putri, Jeni Angela; Apriyani, Eka; Cinta, Lara; Salsabila, Sabrina; Maschamah, Rahmaningrum (Seminar Nasional Lahan Suboptimal, 2024)
Indayani, I., Herlinda, S., Yulistin, E., Setyawati, A., Oktaviani, O., Anggraini, E., Putri, J. A., Apriyani, E., Cinta, L., Salsabila, S., Maschamah, R. (2024). Population and storage pest species from two local markets with various structure and sanitation in sub-district of 7 Ulu and Plaju, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 176–185). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Pest insects in storage are the primary cause of damage to food products in warehouses, leading to a decline in quality and storage outcomes. This study aimed to determine the diversity of insect pests in warehouses across two distinct marketplaces.This research used observational methods, utilizing purposive sampling and data gathering. Observations conducted across many marketplaces indicated that each species exhibited distinct population variability in every assessment of warehouse pest insects within market and warehouse regions. In the regions of 7 Ulu and Plaju, peanut commodities were identified to contain pest bug species such as Tribolium castaneum, Carpophilus dimidiatus, Callosobruchus chinensis, Cryptolestes ferrugineus, and Rhyzopertha dominica. The observations in the Plaju Market region identified pest insect species including Oryzaphilus surinamensis, Tribolium castaneum, Callosobruchus chinensis, Sitophilus oryzae, and C. ferrugineus. Observations at PT Bulog Palembang found pest insect species such as Tribolium castaneum and Sitophilus oryzae. The analysis of data from various surveyed markets indicated that the 7 Ulu market contained 5 species of peanut commodity warehouse pests, the Plaju market also had 5 species of peanut commodity warehouse pests, and the rice warehouse was infested with 2 types of rice commodity warehouse pests. resulting in a decline in both quality and quantity. According to the conducted survey, each market and warehouse should implement effective management of temperature, optimal humidity, appropriate lighting, and sanitation.